Tau Phosphorylation Rates Measured by Mass Spectrometry Differ in the Intracellular Brain vs. Extracellular Cerebrospinal Fluid Compartments and Are Differentially Affected by Alzheimer’s Disease - Barthélemy, Nicolas R. (Front Aging Neurosci, 2019)
Tau protein aggregation into neurofibrillary tangles in the central nervous system contributes to the etiology of certain neurodegenerative disorders, including Alzheimer’s disease (AD). Though the mechanism of tau destabilization is not fully understood yet, tau protein has been found to be hyperphosphorylated in tau aggregates. To investigate this further, we developed a highly sensitive and specific mass spectrometry (MS) method using parallel reaction monitoring (PRM) to identify tau phosphorylation sites. This method enables us to compare the abundance of phosphorylation sites in tau proteins in the brain and cerebrospinal fluid (CSF) in humans with and without AD. We detected 29 distinct phosphorylated tau (p-tau) sites in full-length tau from soluble human brain lysate and 12 sites on truncated tau in CSF, mainly in the mid-domain. Brain soluble tau phosphorylation sites are localized on three domains including a proline-rich mid-domain, the C-terminus, and a cluster on the N-terminal projection domain not previously characterized. Some phosphorylation sites increased in CSF, while others decreased compared to brain. Notably, phosphorylation on T205 and S208, recognized by AT8 antibody defining Braak stages of brain tau aggregation, were not detected in normal brain soluble tau but were found in the CSF. Comparison of the p-tau rates from the brain and the CSF indicated that the abundance of phosphorylated sites varied in a site-specific manner. CSF tau proteins from non-AD participants were significantly hyperphosphorylated on T111, T205, S208, T217 and T231. In AD CSF, hyperphosphorylation on these sites was exacerbated, and phosphorylation on T153 and T175 specifically were detected. This supports the hypothesis that tau hyperphosphorylation could be a physiological process amplified by AD pathology. Conversely, we found that S202 was hypophosphorylated in CSF and was not hyperphosphorylated in AD, demonstrating that p-tau isoforms could have different metabolisms depending on which sites are phosphorylated. These site-specific p-tau rates are independent of tau concentration and distinct of current CSF tau and p-tau assays measuring tau isoforms levels. Targeted MS multiplexing ability and high-throughput capacity lets us envision the use of these new p-tau measurements as promising biomarkers for AD diagnosis and tracking therapeutic responses.